Agroforestry Berbasiskan Jelutung Rawa Dan Tanaman Pinang Pada Masyarakat Desa Bram Hitam Kanan Kecamatan Bram Hitam Kabupaten Tanjung Jabung Barat - Albayudi, Albayudi; Sofwan, Sofwan; Mukhsin, Mukhsin (Jurnal Karya Abdi Masyarakat, 2020)
The potential of peatlands for agriculture is very dependent on the type of vegetation and the substrate or the bottom soil and the condition of the hinterland area (Djaenudin, 2008). Not all types of agricultural crops can adapt to this type of land, only certain types can grow and develop well on peatland types. Peatlands have various characteristics depending on the composition of their formation. An appropriate and ideal development pattern for this land is through an integrated farming system (Sudana, 2005). Jelutung can adapt well to both submerged and non-submerged peat soils, jelutung growth in various planting patterns shows an average increment of 1.7 cm / year. In practice, jelutung is planted after oil palm and areca nut are 2-3 years old. However, cropping patterns in peat soils require quite intensive land treatment in the form of drainage / ditches and imposing. To get optimal productivity from a combination of jelutung with other tree crops, it is necessary to research and observe in depth the feasibility of planting patterns both in terms of biophysical and economic aspects. The agroforestation process and community adoption in planting jelutung on owned land are still hampered by obstacles such as access to land and policy instruments. Limited land causes farmers to prefer plants that have long been cultivated such as coffee, areca nut, rubber, and coconut. Planting areca nut on community-owned peatlands by slightly raising the land to be planted. This is intended to overcome the presence of excess water during the rainy season. In general, areca nuts will begin to bear fruit after the age of 3-4 years. The development of areca nut which is growing rapidly in Jambi Province, especially in Kuala Tungkal Regency is influenced by better and more stable market prices. This is influenced by the development of the areca processing industry in Kuala City. Community service is carried out jointly with the Tani Karya Mandiri group, Bram Itam Kanan Village, Bram Itam District, Tanjung Jabung Barat District, Jambi. The method used in Community Service (PPM) is in the form of counseling together with providing Jelutung Swamp seeds obtained from seed breeders in Muara Jambi and the rest from the location of Peat Protection Forest (HLG) around Bram Itam District intensively and subsequently conducting demonstrations planting between areca nut plants belonging to the village community or farmer groups.